Bone Sarcoma: Treatment by Irradiation, Amputation, or a Combination of the Two. Issue 5758 (15th May 1971) - Sweetnam, Rodney; Knowelden, John; Seddon, Herbert
Abstract : A retrospective survey of all cases of osteosarcoma of the femur and tibia treated at the major centres in the United Kingdom during 1952-9 was carried out in an attempt to assess the respective value of treatment by surgery and radiotherapy and the feasibility of a larger prospective study. Of the 192 patients available for the comparison, those treated by radiotherapy alone did least well. A combination of the two treatments—radiotherapy followed by amputation—produced better results, in terms of survival, than amputation alone; however, the comparatively small numbers involved and the inadequacy of information about the factors dictating the choice of treatment make firm conclusions impossible. A controlled clinical trial on a larger scale might provide answers to the outstanding questions.